2015
DOI: 10.1111/jbi.12539
|View full text |Cite
|
Sign up to set email alerts
|

Competing paradigms of Amazonian diversification and the Pleistocene refugium hypothesis

Abstract: Evidence from butterflies and birds suggests that most extant Amazonian species arose during the Pleistocene (< 2.6 Ma). If these speciation events share common, extrinsic causes, their explanation probably involves climate‐driven biogeographical shifts, because the major orogenic events shaping the biogeography of the Neotropics were over by then. In the light of these observations, criticisms of the Pleistocene refugium hypothesis are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, a recent meta‐analysis suggested that extant Neotropical butterflies are mostly of Pleistocene origin, but the interpretation that the authors of the study gave to this finding was a congruence between timing of butterfly divergence and the refuge hypothesis predictions (i.e., mode of evolution) (Garzón‐Orduña et al. , ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, a recent meta‐analysis suggested that extant Neotropical butterflies are mostly of Pleistocene origin, but the interpretation that the authors of the study gave to this finding was a congruence between timing of butterfly divergence and the refuge hypothesis predictions (i.e., mode of evolution) (Garzón‐Orduña et al. , ).…”
Section: Resultsmentioning
confidence: 96%
“…It has been argued that the ideal datasets to investigate the origin of extant biodiversity must consist only of pairs of sister species because crown group ages may overestimate pre‐Quaternary events (Garzón‐Orduña et al. , ). Here, I retrieved the ages of sister species pairs and their closest extant relative from 5 random trees simulated under each diversification scenario.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fossil provides the earliest constrained age for regional presence of primates (15). Recent discovery of a tick in mid-Tertiary amber, containing blood cells similar to those of primates but not other Caribbean mammals, has been interpreted as evidence of possible primate occurrence on Hispaniola from at least 15 Ma and possibly [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. All other Caribbean primates [Antillothrix bernensis and Insulacebus toussaintiana from Hispaniola, Paralouatta varonai from Cuba, and Xenothrix mcgregori from Jamaica (6,17,18)] are known from late Quaternary cave deposits.…”
Section: Primates Of the Caribbeanmentioning
confidence: 99%
“…The neotropical region is known for its high species richness (Myers et al, 2000), although the processes responsible for this richness remain under debate (see Haffer, 1997; Hoorn et al, 2010; Álvarez-Presas et al, 2014; Fouquet et al, 2015; Garzón-Orduña et al, 2015), and a large part of this diversity is still undescribed (Myers et al, 2000; Fouquet et al, 2007; Giam et al, 2012). Giam et al (2012), based on the analysis of the taxonomic effort dedicated to the description of species over time and the geographic distribution of the described species, estimated that approximately 33% of the species of amphibians were not described at that time, including those in the neotropical forests, a biome supposedly hosting a great part of these unknown species.…”
Section: Introductionmentioning
confidence: 99%